Infusing disability equity within rehabilitation education and practice: A qualitative study of lived experiences of ableism, allyship, and healthcare partnership - Feldner, Heather A.; Evans, Heather D.; Chamblin, Katherine; Ellis, Lesley M.; Harniss, Mark K.; Lee, Danbi; Woiak, Joanne (Frontiers in Rehabilitation Sciences, 2022)
Background Addressing issues of diversity, equity, and inclusion (DEI) has become central in implementing inclusive and socially responsible rehabilitation education and clinical practice. Yet, the constructs of disability and d/Deaf identity and culture, as well as ableism and allyship are often overlooked. Or, these concepts are approached using outdated philosophical perspectives that pathologize disability and fail to prioritize the lived experiences, expertise, intersectionality, and self-identified needs of people with disabilities. A Critical Disability Studies (CDS) framework may provide a background for better understanding and responding to these issues through allyship. Purpose This study employed a CDS framework to understand the lived experiences of ableism and allyship from faculty, staff, and students on University of Washington (UW) campuses who identify as d/Deaf, disabled/with a disability, or as having a chronic health condition. Methods During 2020–2021, we conducted in-depth, semi-structured interviews and focus groups with 22 diverse undergraduate and graduate students, faculty, and staff with disabilities, one third who also identified as people of color. Encounters were audio-recorded, transcribed verbatim, and coded using constant comparison until themes emerged. Results Four major themes that emerged from the data are: (1) Ever-present ableism in healthcare, (2) Ableism at the intersections, (3) COVID: Surfacing ableism and expanding access, and (4) Disability allyship and healthcare partnership building. Experiences of ableism and allyship were identified at individual, group/unit, and institutional/systemic levels, though participants reported significantly fewer instances of allyship compared to experiences of ableism. Participants identified intersections between disability and other marginalized identities and juxtaposed the benefits of widespread adoption of many access-increasing practices and technologies due to the COVID-19 pandemic, while also highlighting ways in which the pandemic created new obstacles to inclusion. Conclusions This analysis provides insights into ways of implementing inclusive practices in rehabilitation education, practice, and beyond. Rehabilitation students, faculty, and staff may not be aware of how ableism affects their disabled peers or underpins their professional education. It is important to cultivate opportunities within professional education and clinical training to explicitly address our collective role in creating inclusive and accessible academic and healthcare experiences for our diverse community post COVID-19. Drawing on a CDS framework, the research team devised the mnemonic TRAC, which includes Training, Recognition and Representation, Attendance and Action, and Calling to account as strategic guidelines for operationalizing such opportunities.